Gender perspectives in disaster response: An evidence-based review - Alfred Acanga; Baker Matovu; Venugopalan Murale; Sudha Arlikatti (Progress in Disaster Science)
An in-depth understanding of diverse gender perspectives, pathways, and frameworks is pivotal for innovative and successful disaster response and resilience strategies across geographies. However, in most regions, gender perspectives in driving disaster resilience are either less operationalized, explored in research, or fragmented, creating unsustainable futures. The ramifications of these inequalities were foregrounded by the COVID-19 pandemic where the disproportionate vulnerability of individuals/genders became unavoidable. This reifies the need to create safety nets within disaster-resilient landscapes based on a gender-inclusive lens. In this study, 80 documents were systematically reviewed to explore the current and emerging gender perspectives (individual and institutional) towards disaster response and resilience mechanisms across geographies and over time. Findings highlight theoretical and conceptual deficits in the definition of gender and disaster response in the discourses. Additionally, disasters and disaster-induced impacts vary over time across genders and regions. They also reveal disproportionate disaster vulnerability among gender minorities and historically marginalized social groups. Furthermore, socioeconomic gender inequalities limit collective agency in disaster response while socio-cultural and patriarchal norms lead to uneven disaster response that are further reinforced by gender inequalities that lead to structural violence. Increased vulnerability to disasters increases fear and mistrust of existing institutional disaster management strategies. Response to Normative disaster management frameworks that entrench masculine dominance in disaster response through, emerging frameworks that draw from a critical feminist lens unfortunately feminize vulnerability and adversely limit gender-inclusive futures. It is acknowledged that place and social capital shape people's willingness to engage in disaster response across genders and regions. Therefore, collective social agency, social networks, and gender inclusion are catalytic towards the efficacy of disaster response and community resilience. Risk Communication for effective disaster response should leverage community institutions like schools, digital media platforms, and indigenous knowledge carriers to generate, mediate, and disseminate appropriate risk information. Five key strategies could drive gender-inclusive perspectives in disaster response and resilience, including (i) conducting context-based studies and research, (ii) use of novel research approaches, such as reflexive social learning, (iii) prioritizing incorporation of collective agency in policy and institutional frameworks, (iv) a research shift and focus towards uncovering the histories of vulnerability, and (v) development of transparent and feasible knowledge dissemination mechanisms. Increased participatory evidence-based research is needed, and policy frameworks must emphasize key pillars of disaster response and integrate them with emerging perspectives on gender empowerment, (e.g., in social, economic, psychological, scientific/technological, institutional, and environmental) arenas.